Non-contrast-enhanced magnetic resonance angiography as part of a kidney pretransplantation work-up in a 19-month-old boy – a case report - Postępska, Agnieszka; Pietura, Radosław; Wieczorkiewicz-Płaza, Anna; Sikora, Przemysław (Pediatria Polska - Polish Journal of Paediatrics, 2023)
Kidney transplantation (KT) is the optimal method of renal replacement therapy in children with end-stage kidney disease. An assessment of the anatomy of the recipient’s abdominal and pelvic vasculature is an element of the pre-KT work-up. We present an uncommon application of non-contrast-enhanced magnetic resonance angiography (NC-MRA) within a pre-KT work-up of a young child with residual kidney function. Due to the history of multiple cannulations of the patient’s femoral veins and the possible risk of inferior vena cava thrombosis, performance of contrast-enhanced computed tomography angiography (CCTA) was requested by the transplantation center. However, considering the significant risk of post-contrast loss of the patient’s residual kidney function, we decided to perform NC-MRA. It accurately confirmed the preserved patency of the arterial and venous vessels of the abdomen and pelvis. We believe that NC-MRA may be considered as an alternative method to CCTA in selected pediatric KT candidates.